Food Choices of Children With Autism Spectrum Disorders - Michelle Ann Suarez; Kristin Marria Crinion (Shiraz University of Medical Sciences, 2015)
Background: Food selectivity is common in children ASD and has significant implications for health and quality of life. Developing more information about the content and quality of the diets of children with ASD and food selectivity could inform treatment. Objectives: The objective of this study was to describe the foods that children with autism and food selectivity eat and to compare the composition of the diets of children with and without food selectivity. Patients and Methods: Data from 54 participants collected during a larger longitudinal survey study was analyzed. Parents of children with ASD completed a food inventory marking foods that their child had accepted over the past month. They also described the particular presentation (e.g. texture, particular plate) required for their child to eat the food. The compositions of the diet including the percentage of each food group in total diet and the percentage of empty calories in the total diet of the food repertoires of the children who accepted 20 or less compared to greater than 20 foods was analyzed using independent t-test. Qualitative descriptions of food presentation were analyzed using a phenomenological method. Results: Parents rated foods from each group and the top rated vegetables and fruits were presented. Children who had 20 or less foods in their diet repertoire had a significantly lower percentage of vegetables and fruits, and a significantly higher percentage of dairy and grain/potato/snack foods than children with more than 20 foods as part of their regular diet. Also, children with 20 or less foods had a greater percentage of empty calories in their total diet compared to the children who had greater than 20 foods. Themes developed from the parents description of food presentation required to accept food included the visual presentation of the food and that food could not be mixed or touch other foods. Conclusions: Information about which foods children with ASD and food selectivity accept could help inform decisions about which foods to introduce first in treatment. The fact that the children with fewer foods in their repertoire have a smaller percentage of whole vegetables and fruits in their total diet and more empty calories may have implications for future health outcomes.